PENERAPAN METODE SAW DALAM SISTEM PENDUKUNG KEPUTUSAN EVALUASI HARGA POKOK SAWIT PTPN IV REGIONAL II - INDAH SARI SIAGIAN; Raden Aris Sugianto; Ritna Wahyuni (LPPM Universitas Abdurrab, 2026)
Determining the Cost of Goods Manufactured (COGM) of processed palm oil products remains a significant challenge for PT Perkebunan Nusantara IV Regional II. The large number of interrelated cost components and the absence of a structured analytical system have caused the evaluation process to be less optimal. This study aims to implement the Simple Additive Weighting (SAW) method in a web-based Decision Support System to evaluate the COGM of Crude Palm Oil (CPO) products. The SAW method was selected due to its ability to objectively assess multiple criteria through normalization, weighting, and preference value calculations. The data used include raw material costs, labor costs, factory overhead costs, and selling prices from January to December 2024, consisting of 12 production month alternatives and 4 main criteria. The results showed that the SAW method was able to generate a ranking of production cost efficiency, where September obtained the highest preference value of 0.8407, while August had the lowest value of 0.5861. The developed system has passed validation testing with 100% conformity to manual calculations and successfully passed functionality testing using the black box method. Therefore, the implementation of the SAW method has proven effective in assisting management in evaluating COGM more quickly, objectively, and measurably, as well as supporting decision-making related to production cost efficiency at PT Perkebunan Nusantara IV Regional II.